2010
DOI: 10.1063/1.3383052
|View full text |Cite
|
Sign up to set email alerts
|

Envelope ion-acoustic solitary waves in a plasma with positive-negative ions and nonthermal electrons

Abstract: Modulation instability of ion-acoustic waves is investigated in a plasma composed of positive and negative ions as well as nonthermal electrons. For this purpose, a linear dispersion relation and a nonlinear Schrödinger equation are derived. The latter admits localized envelope solitary wave solutions of bright-(pulses) and dark-(holes, voids) type. The envelope soliton depends on the intrinsic plasma parameters. It is found that modulation instability of ion-acoustic waves is significantly affected by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…Both distributions have been found to exist in space plasma environments [15][16][17][18][19][20] and applied to the study of certain types of acoustic solitons. [21][22][23] Observational evidences for electrostatic acoustic solitons in the space and laboratory are overwhelming [24][25][26][27][28][29] and the identification of various types of solitons is usually based on standard models assuming Maxwellian distribution. It is important to incorporate more realistic non-Maxwellian distribution in the model calculations and to examine how the characteristics of acoustic solitons such as the polarity of electric potential as well as the number density profile may depend on the distribution functions.…”
Section: Introductionmentioning
confidence: 99%
“…Both distributions have been found to exist in space plasma environments [15][16][17][18][19][20] and applied to the study of certain types of acoustic solitons. [21][22][23] Observational evidences for electrostatic acoustic solitons in the space and laboratory are overwhelming [24][25][26][27][28][29] and the identification of various types of solitons is usually based on standard models assuming Maxwellian distribution. It is important to incorporate more realistic non-Maxwellian distribution in the model calculations and to examine how the characteristics of acoustic solitons such as the polarity of electric potential as well as the number density profile may depend on the distribution functions.…”
Section: Introductionmentioning
confidence: 99%
“…The results from this investigation can be summarized as follows: we hope that the results of this theoretical investigation may be helpful in understanding the MI of IAWs and generation of IARWs in laboratory plasmas, viz., PI fullerene (C + , C − ) [4] or in the space plasma, viz., D-region (H + , O − 2 ) and F-region (H + , H − ) of the Earth's ionosphere, [3] Titan's atmosphere, [2] etc. The evolution of the IAWs is governed by the standard NLSE, and the non-linear P and the dispersive Q coefficients represent the stable/unstable domain of the IAWs in presence of the external perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…The painstaking observational results support the existence of multi-pair plasmas (MPPs) not only in space environments, viz., cometary comae, [1] chromosphere, upper regions of Titan's atmosphere, [2] solar wind, and D-region (H + , O − 2 ) and F-region (H + , H − ) of the Earth's ionosphere [3] but also in laboratory situations, viz., fullerene (C + , C − ), [4] plasma processing reactors, [5] neutral beam sources, [6] etc. Plasma physicists solely deal with the wave dynamics, basically of ion acoustic (IA) waves (IAWs) in which the restoring force is provided by thermal pressure of the electrons and positrons and the moment of inertia is provided by the pair-ion (PI) mass density [7][8][9][10][11] in the PI plasma medium (PIPM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barkan et al (1996) observed the DIAWs experimentally. Furthermore, many efforts have been made to understand the properties of linear and nonlinear DIAWs in dusty plasmas (see e.g., Popel and Yu 1995;Nejoh 1997;El-Labany et al 2003;Ali et al 2008aAli et al , 2008bSayed et al 2008;Mamun et al 2009aMamun et al , 2009bElwakil et al 2010;ElLabany et al 2011aElLabany et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%